Educação estatística crítica na formação do engenheiro ambiental - Evangelista, Dilson Henrique Ramos [UNESP] (2015)
Exploratory research aimed to discuss and analyze the impact of work with statistical modeling projects in the teaching and learning of statistics in course of Environmental Engineering, considering the socio-critical perspective of education. The Education Statistics Critical values the role that education statistics on the development of democratic capacity of citizens. The methodology is based on a qualitative research approach, from the day of field research, with the data collected in two participating classes for Statistic II discipline of the Federal University of Rondônia. Through this research, we observed the importance of providing conditions for students to perform collaborative projects to develop themselves autonomously in order to build knowledge itself, from the boldness of search, research, and transforming thus the exercise of thinking about building. It was concluded that this environment favored the significant critical learning, promoted collaborative work, interdisciplinarity, and contributed to the socio-critical environmental education of students turning them to exercise critical citizenship. The students developed an investigative, reflective and critical attitude when working with real situations of interest by modeling projects